2019
DOI: 10.1371/journal.pone.0210992
|View full text |Cite
|
Sign up to set email alerts
|

Human frozen-thawed blastocyst morphokinetics observed using time-lapse cinematography reflects the number of trophectoderm cells

Abstract: Recent studies reported morphokinetic indices for optimal selection of embryos in assisted reproductive technology (ART). The morphokinetics in blastocyst stage include the collapse and re-expansion rates after thawing. However, evaluation methods using these morphokinetics have not been established, mainly because the underlying molecular mechanisms remain unclarified. In this study, we focused on the relationship between these morphokinetic observation of the blastocyst behaviour and the number of cells cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…SSEA1 is detected in the ICM of mouse and pig embryos, 13 whereas SSEA3, SSEA4, TRA‐1‐60, TRA‐1‐81 and GCTM‐2 were expressed in ICM of human blastocysts 14 . Furthermore, OCT4 expression in mouse blastocysts is limited to the ICM, whereas OCT4 in porcine and human blastocysts is expressed in both the ICM and TE 15‐17 . In addition, the signalling required for maintaining the pluripotency of mouse ESCs differs from species to species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSEA1 is detected in the ICM of mouse and pig embryos, 13 whereas SSEA3, SSEA4, TRA‐1‐60, TRA‐1‐81 and GCTM‐2 were expressed in ICM of human blastocysts 14 . Furthermore, OCT4 expression in mouse blastocysts is limited to the ICM, whereas OCT4 in porcine and human blastocysts is expressed in both the ICM and TE 15‐17 . In addition, the signalling required for maintaining the pluripotency of mouse ESCs differs from species to species.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Furthermore, OCT4 expression in mouse blastocysts is limited to the ICM, whereas OCT4 in porcine and human blastocysts is expressed in both the ICM and TE. 15 , 16 , 17 In addition, the signalling required for maintaining the pluripotency of mouse ESCs differs from species to species. While leukaemia inhibitory factor and bone morphogenetic protein 4 signalling play crucial roles in maintaining the pluripotency of mouse ESCs, 18 in humans, ESC pluripotency is maintained through extracellular signal‐regulated kinase and ACTIVIN/NODAL signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that blastocyst-stage embryo morphology is associated with euploidy, especially concerning ICM and TE parameters (Wang et al, 2016;Barash et al, 2017). The reduced number of TE cells can be attributed to cell division failure due to organelle and chromosomal abnormalities, especially aneuploidy (Iwasawa et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Human blastocysts are constituted by approximately 300 cells; 8 however, to this day, no study has determined the extent to which the 5 biopsied TE cells represent the chromosomal status of the whole blastocyst. As is known, TE cells differentiate into placental tissues after implantation.…”
Section: Introductionmentioning
confidence: 99%